2006
DOI: 10.1007/s00125-006-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosiglitazone and metformin on pancreatic beta cell gene expression

Abstract: Aims/hypothesis: Rosiglitazone and metformin are two oral antihyperglycaemic drugs used to treat type 2 diabetes. While both drugs have been shown to improve insulin-sensitive glucose uptake, the direct effects of these drugs on pancreatic beta cells is only now beginning to be clarified. The aim of the present study was to determine the direct effects of these agents on beta cell gene expression. Methods: We used reporter gene analysis to examine the effects of rosiglitazone and metformin on the activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…The improved insulin secretory profile after RC might be explained by the 'β-cell recruitment' phenomenon in which the detection of increased extracellular glucose by a few individual β-cells initiates the insulin secretory cascade and recruitment of adjacent β-cells to participate in insulin secretion. 54 Additionally, TZDs have been shown to support β-cell function and viability, [34][35][36] and our data corroborate these findings under both SC and RC conditions. While β-cells did not show an additive increase in insulin secretion in response to the combined effects of RC and exposure to a TZD, there was an additional increase in measured soluble VEGF-A release from the combined RC + TZD treatment group.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The improved insulin secretory profile after RC might be explained by the 'β-cell recruitment' phenomenon in which the detection of increased extracellular glucose by a few individual β-cells initiates the insulin secretory cascade and recruitment of adjacent β-cells to participate in insulin secretion. 54 Additionally, TZDs have been shown to support β-cell function and viability, [34][35][36] and our data corroborate these findings under both SC and RC conditions. While β-cells did not show an additive increase in insulin secretion in response to the combined effects of RC and exposure to a TZD, there was an additional increase in measured soluble VEGF-A release from the combined RC + TZD treatment group.…”
Section: Discussionsupporting
confidence: 85%
“…43 The molecular mechanism pertaining to increased insulin secretion following exposure of islets to rosiglitazone has been studied by a number of groups. Richardson et al 35 have shown that rosiglitazone induced the nuclear accumulation of insulin promoter factor 1 (IPF1) and forkhead homeobox A2 (FOXA2), independent of glucose concentration, and also resulted in a twofold increase in the activity of the IPF1 gene promoter. Yang et al exposed islets to high levels of free fatty acids that caused a significant reduction in insulin receptor substrate-2 (IRS-2) protein and the association of IRS-2 with the p85 subunit of phosphatidylinositol 3-kinase (PI 3-kinase), resulting in increased basal insulin secretion and reduced glucose-stimulated insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLP-1 has also been shown to increase PDX1 gene expression in ductal cells during the regeneration of pancreas (Sharma et al, 1999). A similar line of action has been proposed for thiazolidinediones in the enhancement of neogenic beta cell function through activation of nuclear receptor peroxisome proliferator activator gamma (PPAR) (Richardson et al, 2006) …”
Section: Beta Cell Regenerationmentioning
confidence: 73%
“…Finally, pancreatic islets have been shown to express both PPAR␣ and PPAR␥ (Yoshikawa et al, 2001;Rosen et al, 2003;Lin et al, 2005;Park et al, 2006;Richardson et al, 2006). It is possible that muraglitazar may protect ␤-cells directly by favorably altering the expression of PPAR␣-or PPAR␥-target genes, which are implicated in important functions, such as glucose sensing, fatty acid transport, control of cell differentiation, apoptosis, and insulin secretion in ␤-cells (Yoshikawa et al, 2001;Rosen et al, 2003;Lin et al, 2005;Park et al, 2006;Richardson et al, 2006).…”
Section: Muraglitazar Prevents the Natural Progression Of Diabetes 113mentioning
confidence: 99%